Lung Function in Traditional Breath-Hold Diving Fishermen at Impos Beach, Medana District, North Lombok, West Nusa Tenggara - Widiastuti, Ida Ayu Eka; Susani, Yoga Pamungkas; Affarah, Wahyu Sulistya; Wardoyo, E. Hagni; Rahmat, Basuki; Haryanto, Wawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
West Nusa Tenggara is an archipelago province with a high potential for marine resources and fisheries, allowing many inhabitants to make a living as fishermen. Some fishermen obtain their livelihood by diving with minimal or inadequate diving equipment. They are known as traditional diver fishermen. Various health risks can be experienced by them, including respiratory system health. This research aims to determine the lung function, including Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV1), and the FEV1/FVC ratio in traditional diver fishermen who dive using the breath-hold diving technique, as well as the characteristics of their diving activities. This research is a cross-sectional study with samples obtained through consecutive sampling techniques. The research subjects comprised 23 traditional diver fishermen in Impos Beach, Medana Sub-district, North Lombok District. A descriptive analysis was conducted on the data obtained. The research results showed that the average values of FVC and FEV1 were 3.27 L/minute and 3.004 L/minute, respectively, while the FEV1/FVC ratio obtained was 91.86%. On average, they dive 4.26 times per week, and all of them perform pressure equalization maneuvers to prevent barotrauma. Before diving, 12 subjects (52.17%) performed warm-up exercises, including stretching. After diving, none of the subjects take a hot shower, get a massage, or engage in strenuous activities. The lung function of the research subjects was normal, and they have taken preventive measures to avoid diving-related illnesses.